Conducting research in educational contexts - Basit, Tehmina N. 4 0 16; 5 (London ;;New York : Continuum, 2010)
A guide to educational research, providing a detailed overview of the research process from the beginning to gathering and analyzing the collected data, and discussing models and traditions, the role of theory, ethics, interviews, observation, composing a written argument, and other related topics.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Research;Methodology. -- Education -- 20; 20; 2